Mungkinkah untuk menerapkan Activity Based Costing/Management pada Organisasi Pemerintah? Sebuah Tinjauan Pustaka - Sarumaha, Sudarman Ifolala; Pitoyo, M. Muflik Teguh Yuli (E-Jurnal Akuntansi; Vol 33 No 5 (2023), 2023)
As one of the management tools in private sector organizations, Activity Based Costing/Management (ABC/M) provides information and knowledge to make decisions. This study aims to propose an idea of the possibility of implementing ABC/M in government organizations. The research was conducted using a Systematic Literature Review approach. The author collects various articles from reputable journals and proceedings using the Google Scholar database. The selection of articles was adjusted to predetermined inclusion and exclusion criteria. A total of 30 selected articles were analyzed and synthesized. The findings show that the ABC/M system is very likely to be applied to government sector organizations. Reflecting on the successful implementation of the ABC/M method in the public sector, the authors found that the implementation process was not easy. This is supported by the findings of various challenges and obstacles faced by public sector organizations. This research contributes to convincing policy makers that the ABC/M method can be implemented and theoretically contributes to enriching the ABC/M theoretical literature in the public sector, especially in the government sector. Keywords : Activity-Based Costing (ABC); Activity-Based Management (ABM); Government Organizations